P855 Vegetarian and gluten-free diet in patients with IBD—associated with a different microbiota compared with omnivore IBD patients. (16th January 2018) - Schreiner, P; Yilmaz, B; Franc, Y; Rossel, J -B; Misselwitz, B; Scharl, M; Zeitz, J; Frei, P; Greuter, T; Vavricka, S; Pittet, V; Siebenhüner, A; et al.
Abstract: Background: Several studies demonstrate a lower diversity in the gut microbiota of patients with inflammatory bowel disease (IBD). Microbial alterations induced by dietary changes are amongst the key suspected responsible environmental factors to promote an increase in the incidence of IBD, and may adversely impact the course of established disease. Subsequent to our already presented results of lower psychosocial wellbeing in vegetarian diet (VD) and gluten-free diet (GFD) IBD patients (Poster 711, ECCO 2017) we investigated comparative microbial composition of IBD patients according to diet. Methods: Dietary pattern was analysed in a total of 1656 IBD patients from the Swiss Inflammatory Bowel Disease Cohort Study between 2006 and 2015. Microbiota composition was analysed in 149 patients, including 12 vegetarian patients and 14 patients following a GFD by means of high-throughput sequencing. Within the majority of meat-eating patients, we further compared the microbiota of the low vs. high-meat-intake patients (i.e. ≤ 4 vs. >4 days per week). Results: In the alpha diversity analysis (Shannon) we observed a significant difference between GFD and meat-eating Crohn's disease (CD) patients with lower species richness in meat-eating patients ( p = 0.026). In the ulcerative colitis (UC) group no significant difference in the alpha diversity was seen. Both CD and UC revealed significantly different β diversity in meat-eating patients compared with their VD and GFD counterparts. Bacterial taxa did not differ according to diet types in CD, whereas within meat-eating CD patients the following significant differences in taxa were found: Faecalibacterium, Bilophila and Butyricimonas taxa were found to be less abundant in the high-meat-intake CD group. On the other hand, there was a higher relative abundance of Eubacterium (family Erysipelotrichaceae), Enterococcum, Lactobacillus, Lactococcus, Fusobacterium, and Tepidimonas in the high-meat-intake CD group. In UC meat-eating patients there was a significantly higher relative abundance of Ruminococcus compared with GFD and VD patients. The high-meat-intake UC patients had a higher relative abundance of Lachnospira, Ruminococcus, and Parabacteroides. Conclusions: The gut microbiota composition in meat-eating IBD patients is significantly different compared with those following a VD or GFD. The potentially anti-inflammatory taxa Faecalibacterium and Butyricimonas were reduced and the inflammatory taxa Erysipelotrichaceae and Enterococcus were increased in the high-meat-intake CD patients. Our results demonstrate several bacterial changes in regularly meat-eating IBD patients compared with VD or GFD, specifically lower species richness with a dose–response effect in meat-eating CD patients.